WORKING CAPITAL TURNOVER, OPERATIONAL COST RATIO, AND INVENTORY TURNOVER ON COMPANY PERFORMANCE - Ajeng Eka Pratama; Muhaimin Dimyati; Yanna Eka Pratiwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study aims to determine the effect of working capital turnover, operational cost ratio, inventory turnover on the performance of UD. Firmansyah. The data used are the financial statements for the period 2015-2018. The data obtained were analyzed using multiple linear regression. The number of samples used was 48 samples. Partially the results show that working capital turnover and inventory turnover do not have a significant effect on company performance, while the ratio of operating costs has a significant effect on company performance. Meanwhile, simultaneously the research shows that working capital turnover, operational cost ratio, and inventory turnover have a significant effect on company performance. The coefficient of determination in this study is 0.165, which means that 16.5% of the company's performance can be explained by working capital turnover, operational cost ratio, and inventory turnover variables. At the same time, the remaining 83.5% is explained by other factors not included in this study.